2011
DOI: 10.1063/1.3657023
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Inlet for a Laser Powered Propulsion System

Abstract: Abstract. Propulsion within the lightcraft concept is produced via laser induced detonation of an incoming hypersonic air stream. This process requires suitable engine configurations that offer good performance over all flight speeds and angles of attack to ensure the required thrust is maintained. Stream traced hypersonic inlets have demonstrated the required performance in conventional hydrocarbon fuelled scramjet engines, and has been applied to the laser powered lightcraft vehicle. This paper will outline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To obtain optimal supersonic mode of the LIGHT-CRAFT operation, the condition of precise pressure recovery of gas flow in the slit inlet in dependence of the incoming flow Mach number is determined [22]. The forebody surface is shaped in such a way that a bow shock wave arising in supersonic flow directs incoming flow into the slit nozzle without additional pressure losses and shocks (Fig.…”
Section: Supersonic Laser Propulsion Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain optimal supersonic mode of the LIGHT-CRAFT operation, the condition of precise pressure recovery of gas flow in the slit inlet in dependence of the incoming flow Mach number is determined [22]. The forebody surface is shaped in such a way that a bow shock wave arising in supersonic flow directs incoming flow into the slit nozzle without additional pressure losses and shocks (Fig.…”
Section: Supersonic Laser Propulsion Featuresmentioning
confidence: 99%
“…But the experiments carried out by the authors demonstrated essential instability of thrust production in this case. Analysis of the experiments shows that the technique of thrust production imposes mutual constraints on laser characteristics as a function of flow parameters [16].…”
Section: Introductionmentioning
confidence: 99%